The course of coronavirus pneumonia in a teenager from the focus of infection - L. N. Mazankova; I. M. Osmanov; E. R. Samitova; A. A. Nedostoev; S. O. Kotenko; O. S. Kulichkina (LLC "Diagnostics and Vaccines", 2020)
A new coronavirus infectionin children in most cases is easier than in adult patients, however, some cases are characterized by a protracted course and duration of the release of SARS-CoV-2 virus.The article presents own data monitoring of children with novel coronavirus infection with clinical case COVID-1 9- pneumonia, which appeared to slow reverse the development of infiltrative changes in the lungs according by the type of «frosted glass» on computed tomography on the background of the relief of clinical symptoms of pneumonia negative results of smears from the oropharynx and nasopharynx on the determining of RNA of SARS - Cov-2 by PCR and a positive serological response in the form of increase of IgG-antibodies to COVID-1 9 with negative IgM-antibodies.